Integrated rural development as a means for development benefit to Asia small farmers - Chang, H.T (1977)
The Asian small farmers must be reached directly if they are to share in the benefits of development. In order to reach them, channels must be built for delivery of goods, technology, services and credit. Farmer organizations are essential links in this delivery system and, thus, are crucial to rural development. In the long run, rural development must embrace all activities for the betterment of rural livelihood, However, to lump many activities of a different nature together and call the product "integrated" has led to the failure of many projects. True integration should be built around activities directed at solving critical farm level problems faced by large numbers of farmers.